In memoriam of Raymond Pahl Whose modern megalopolises? - Yanitsky, Oleg N. (Advances in Social Sciences Research Journal, 2017)
The ‘whose city?’ question is acute today. The article is a brief inquiry in the meaning of this question posed by the UK sociologist R. Pahl in the early 1970s and to point out the changes in urban studies during the last decade. His appeal for a cumulative, systematic approach as well as for resistance against futuristically-oriented market research and a dictate of the developers are still valid. A growing social inequality issue is today as important as half-a-century ago. Describing the ontological premises of the concept of modern megalopolises, the following structures and processes should be taken into account: modern megalopolises are the sociobiotechnical systems (the SBT-systems) dependent on the global SBT-system which in turn tightly integrated by the information-communication technologies (IC-technologies); all kinds of them are interconnected by socio-ecological metabolic processes; modern megacities are involved into global geopolitical processes aimed at gaining new resources and political domination, and post-socialist megacities are involved in it; and the struggle between two adversarial trends – globalization/unification and localization/particularization—will continue. Therefore, there is no single ‘owner’ of such megacities.